1998
DOI: 10.1002/(sici)1096-9063(199809)54:1<27::aid-ps772>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Action of the ecdysteroid agonist tebufenozide in susceptible and artificially selected beet armyworm

Abstract: : Toxicity assays with tebufenozide, the Ðrst commercial non-steroidal ecdysteroid agonist, against a laboratory strain of the beet armyworm, Spodoptera exigua (Hu bner), demonstrated the promise of this new compound for the control of this important pest. Experiments to select insects artiÐcially from the laboratory strain by continuous exposure of larval instars to corresponding LC 25 doses of tebufenozide for over 12 generations 14È15 months), (G 0 ] G 12 : revealed no loss in susceptibility to the insectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 28 publications
4
28
0
1
Order By: Relevance
“…26) Hence, for practical application, the use of crude extract may be better than using an isolated compound because ricinine is toxic to mammals 27) and crude extract may have other active compounds that can interact and synergize 5 of ethyl acetate J. gossypifolia extract by the dipping method, for which the control group was 70% ethanol. (1) After monitoring the components from eluted solution using TLC, 20% dichloromethane:hexane could be separated into two fractions (I and II); similarly, 70% dichloromethane:hexane could be separated into two fractions (II and III). each other to increase control effectiveness against S. exigua.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26) Hence, for practical application, the use of crude extract may be better than using an isolated compound because ricinine is toxic to mammals 27) and crude extract may have other active compounds that can interact and synergize 5 of ethyl acetate J. gossypifolia extract by the dipping method, for which the control group was 70% ethanol. (1) After monitoring the components from eluted solution using TLC, 20% dichloromethane:hexane could be separated into two fractions (I and II); similarly, 70% dichloromethane:hexane could be separated into two fractions (II and III). each other to increase control effectiveness against S. exigua.…”
Section: Discussionmentioning
confidence: 99%
“…Due to heavy selection pressure over the past two decades, the pest has developed resistance to various insecticides in many countries. [1][2][3][4] Recently, in order to circumvent this problem, several biopesticides have been developed. Among these, several works have referred to the efficacy of semiochemicals from plant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As ecdysone agonists, these manifest their toxic action via interaction with ecdysteroid-receptor complex of target species. RH-5992 (Tebufenozide) had undergone a considerable field evaluation and had proven to be very efficient in controlling lepidopteran pests in orchards, vineyards, vegetable field and forests and marketed under the brand name MIMIC , CONFIRM , ROMDAN (Smagghe et al 1998). RH-5992 was reported to have high potential in integrated pest management as it exhibited low toxicity to non-target species like mammals, birds, and fishes and is considered safe to beneficial arthropods, parasitoids and predators.…”
Section: Introductionmentioning
confidence: 99%
“…Although insects are capable of resisting toxic effects of insecticides through a variety of defence mechanisms, the most important route of insecticide resistance is in many cases an enhanced detoxifying metabolism. For tebufenozide, a previous study indicated that oxidation is a major route of breakdown in artificially selected larvae of S. exigua ( Smagghe et al., 1998b).…”
Section: Introductionmentioning
confidence: 99%